(untitled) (Journal of Global Arts Studies, 2024)
Background: The comfort demand of game and animation creative talents in Guangfo region is an important factor affecting the talent gathering ability in the region. Objective: The comfort requirements of game and animation creative talents in the region were collected statistically in the early stage, the types of comfort facilities were analyzed, and the comfort facilities were optimized according to the characteristics. Methods: through expert consultation and the sampling interview confirmation to form the 17 comfortable physical characterization factors of demand. According to the above requirements, the Kano questionnaire is designed and analyzed to define the comfort demand type of talents. Results: The study found that the cultural venues and activities segment had an expectation, charm, and no difference demand dimension; the work environment demand item had both essential and charm demand; the living convenience facilities segment was mainly composed of expectation demand; and the social communication facilities and health and leisure facilities covered essential, expectation, and charm demand. Conclusion: Based on the research findings, the factors that meet the needs of talents for comfort are defined, and the optimization of the path of attracting talents in related industries is proposed.However, due to the limited sample size of data collection, the scientific nature of its research needs to be further improved.